Sobre o brilhante efeito: história e narrativa visual na Amazônia em Antônio Parreiras (1905 – 1908) - CASTRO, Raimundo Nonato de (Universidade Federal do Pará, 2014)
The screen A Conquista do Amazonas by Antônio Parreiras seeks to represent the Lusitanian dominion over Amazonian people, demonstrating the sovereignty of white people, a fact essential for the initiation of the Brazilian Republic. In this case, the picture is an attempt to revive the great Lusitanian achievements, using an analogy, as if the Republican establishment gains grand scales, characteristic of European conquests of the colonial period. Therefore, having a last fact, capable of generating a unity, it was considered essential to the formation of a nation. Being characterized as a spiritual principle, considered sacred and based on a heroic past. In this case, the nation was a large-scale solidarity, constituted of the perception of the sacrifices made in the past. The artist played a key role in seeking the origins of the existence of the nation, imagining it, so, to present it to the citizens, confronting them, even in the most distant locals of the nation.